Building Creative Capacity Building in University Graduates: What we can learn from boids and voids - McWilliam Erica (Cultural Science)
This paper draws on recent computing and social organizational research to open up new possibilities for constructing learning environments that optimise opportunities for university students (and, indeed, their teachers) to work as members of dynamic creative teams. Given that the challenge of setting up a learning environment that fosters such a complex mix of relational dynamics is not a simple matter of ensuring that people feel good about themselves, the paper canvasses two areas of research that can be usefully bought together to provide principles on which to build learning environment for ‘high flying’ creatives.